Sleep Status and Chronotype in University Athletes with and without Chronic Low Back Pain: A Cross-Sectional Study - Ansari, Sumbul; Sharma, Saurabh (Sleep science (Sao Paulo, Brazil), 2024)
Objective This study aimed to evaluate the status of sleep, chronotype, and related variables of university athletes with and without chronic low back pain (CLBP), to find the correlation between CLBP, sleep difficulty score (SDS), and chronotype, and to determine if SDS and chronotype predict CLBP. Methods Ninety-two university athletes [46 with CLBP (Age: 22.08±2.74 years) and 46 healthy athletes (Age: 22.32±3.11 years) completed the athlete sleep screening questionnaire (ASSQ), also, their demographic, anxiety, depression, and sports-related details were collected. A Pearson correlation and logistic regression models (univariate and multivariate) were used for the statistical analysis. Results The results demonstrated a higher SDS and evening type preference in CLBP athletes, a significant negative correlation between CLBP and chronotype (r = −0.40, p<0.01), a significant correlation between SDS and CLBP (r = 0.25, p = 0.01). SDS and chronotype were not found to be significant independent predictors of CLBP. Conclusion This study concludes that there exists a correlation of CLBP, SDS, and chronotype However, despite the relationship, SDS and chronotype cannot predict CLBP.